Highly Stable Doped Barium Niobate Based Electrocatalysts for Effective Electrochemical Coupling of Methane to Ethylene. Issue 27 (26th August 2022) - Denoyer, Luke H.; Benavidez, Angelica; Garzon, Fernando H.; Ramaiyan, Kannan P.
Abstract: Methane conversion into value‐added products such as olefins and aromatics is gaining increased attention in the wake of new natural gas reserve discoveries. Electrochemical oxidative coupling of methane (E‐OCM) provides better product selectivity as the product distribution can be controlled by applied potential as well as the oxide ion flux. Here a new catalyst based on Mg and Fe codoped barium niobate perovskites is reported. The prepared perovskites show excellent chemical stability in CH4 ‐rich environments up to 925 °C while showing methane activation properties from 600 °C. E‐OCM measurements indicate an ethylene production rate of 277 µmol cm −2 h −1 with a faradaic efficiency of 20% at 1 V and durable operation for six continuous days. X‐ray photoelectron spectroscopic measurements indicate significant Nb valency reorganization that can be the reason for its chemical stability. Nevertheless, the surface area of the catalyst is significantly lower and requires improvements in synthesis methodologies to improve catalytic activity further. The exceptional chemical stability of this perovskite material under methane exposure at high temperatures has significant importance as this material can be used as a catalyst and/or support in a wide variety of applications relevant for efficient energy conversion and storage. Abstract : Fe and Mg codoped barium niobate perovskites are prepared by a solid‐state method. The perovskite materials show very good chemical stability under carburizing environments and show methane activation properties starting at 600 °C. Both oxidative coupling and electrochemical oxidative coupling measurements show high C2 selectivity under extreme conditions.